2006
DOI: 10.1083/jcb.200604031
|View full text |Cite
|
Sign up to set email alerts
|

Transport of PIP3 by GAKIN, a kinesin-3 family protein, regulates neuronal cell polarity

Abstract: Phosphatidylinositol-(3,4,5)-trisphosphate (PIP3), a product of phosphatidylinositol 3-kinase, is an important second messenger implicated in signal transduction and membrane transport. In hippocampal neurons, the accumulation of PIP3 at the tip of neurite initiates the axon specification and neuronal polarity formation. We show that guanylate kinase–associated kinesin (GAKIN), a kinesin-like motor protein, directly interacts with a PIP3-interacting protein, PIP3BP, and mediates the transport of PIP3-containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
151
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(163 citation statements)
references
References 51 publications
4
151
3
1
Order By: Relevance
“…We reported previously that PIP 3 seems to be transported toward the contact site . In fact, Horiguchi et al (2006) recently demonstrated that a complex of guanylate kinase-associated kinesin and a PIP 3 -interacting protein, PIP 3 BP, transports PIP 3 to the neurite end. The phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a lipid and protein phosphatase that functions in an opposite manner from PI3-kinase by dephosphorylating PIP 3 (Maehama and Dixon, 1998).…”
Section: Pi3-kinase/akt/gsk-3␤ Pathwaymentioning
confidence: 99%
“…We reported previously that PIP 3 seems to be transported toward the contact site . In fact, Horiguchi et al (2006) recently demonstrated that a complex of guanylate kinase-associated kinesin and a PIP 3 -interacting protein, PIP 3 BP, transports PIP 3 to the neurite end. The phosphatase and tensin homolog deleted on chromosome 10 (PTEN) is a lipid and protein phosphatase that functions in an opposite manner from PI3-kinase by dephosphorylating PIP 3 (Maehama and Dixon, 1998).…”
Section: Pi3-kinase/akt/gsk-3␤ Pathwaymentioning
confidence: 99%
“…6 A, B, D, E). This truncated form of kif13B has been used previously to demonstrate that kif13B transports Dlg1 to the tip of MDCK cell projections (Asaba et al, 2003) and PtdIns(3,4,5)P 3 (also known as PIP 3 ) to the tips of growing neurons through a PIP 3 BP (PIP 3 -binding protein) complex (Horiguchi et al, 2006). Following on the hypothesis that, in Schwann cells, kif13B transports Dlg1 at nodal-paranodal regions, first we quantified Dlg1 staining in myelinated fibers.…”
Section: Dlg1 Interacts With Kif13b and Sec8 In Schwann Cells In The mentioning
confidence: 99%
“…Various mechanisms have evolved to establish and maintain cellular polarity, which, in most cases, are based on asymmetrical distribution of specific proteins or on higher-order organization of cellular structures. Recently, the Par (Partition-defective) family of proteins has frequently been assigned an essential role in mammalian systems, notably in axon polarization (Benton and Johnston, 2003;Shi et al, 2003), but other protein families have also been implicated, namely, proteins in the PI 3 K-associated pathway (Horiguchi et al, 2006) and small GTPases (Wells et al, 2006). Despite increasing insight into the regulatory interactions of these proteins, some fundamental aspects still need to be resolved as, in most reports, the mechanisms through which polarization is achieved and maintained are not established.…”
Section: Introductionmentioning
confidence: 99%